Ursolic Acid Inhibits Collagen Production and Promotes Collagen Degradation in Skin Dermal Fibroblasts: Potential Antifibrotic Effects - He, Tianyuan; Xiang, Yaping; Quan, Hehui; Liu, Yingchun; Guo, Chunfang; Quan, Taihao (Biomolecules (Basel, Switzerland), 2025)
Tissue fibrosis, characterized by excessive collagen accumulation, leads to impaired organ function and is a hallmark of various chronic diseases. Fibroblasts play a central role in collagen production and deposition. This study examines the impact of ursolic acid, a pentacyclic triterpenoid compound present in various fruits and vegetables, on collagen homeostasis in primary human dermal fibroblasts. Ursolic acid (UA) was observed to significantly reduce collagen production while markedly increasing the activity of matrix metalloproteinase-1 (MMP-1), an enzyme responsible for collagen degradation. Mechanistically, ursolic acid was found to inhibit TGF-β/Smad signaling, leading to decreased collagen production, and to activate mitogen-activated protein kinase (MAPK) pathways and activator protein 1 (AP-1), resulting in enhanced MMP-1 production. These in vitro findings were further validated in an in vivo mouse model of fibrosis, where ursolic acid significantly mitigated bleomycin-induced skin fibrosis. These results suggest that UA could be a promising candidate for treating skin fibrosis due to its dual effects on collagen homeostasis: inhibiting collagen production and promoting collagen degradation.